COMPLIANCE TO DIABETIC MANAGEMENT AMONGST PATIENTS WITH DIABETES MELLITUS ATTENDING A GOVERNMENT HOSPITAL IN KANO, NORTHWESTERN NIGERIA - LAWAN UM; TANIMU N; GADANYA MA (Ntec Specialist, 2008)
Background: The physical, social, and economic burden of diabetes mellitus result mostly from the complication of the disease, which occur because of poor compliance to treatment. However, physicians commonly ignore this important aspect of diabetic management. This study assessed patients' compliance to diabetic control measures using a combination of direct and indirect approaches. Objectives: The study aimed to assess diabetic patients' compliance to management, as well as the sociodemographic factors influencing their compliance. Methods: A cross sectional design was used to study 240 systematically selected diabetic patients from the diabetic Clinic of a General Hospital. Subjects were interviewed using a semi-structured interviewer administered questionnaires, and data generated were analyzed using "Mini tab" 12.21 computer statistical software. Patients compliance was assessed using regularity of appointment visit, dietary control, regularity on drugs, modification of life style, and scored using a Likert scale. Resulls: More than one-third (37.1%) of the diabetic patients had good compliance to diabetic management, whereas 41.3% and 21.6% of them had moderate and poor compliance respectively. Compliance however varied for the different methods used to control the disease, with compliance to drugs use being highest. The sex of the patients, their educational status, occupation, and their average monthly incomes were found to significantly influence the patients' compliance to diabetic management. Conclusion: This study demonstrates that diabetic patients are being selective on the use of disease control measures prescribed to them by their physicians.